Main Principles of Using Audiovisual Method in Teaching the Native Language to Children of Pre-School Age in the Ukrainian Diaspora of the USA and Canada - Rudnytska-Yuriichuk, Iryna (Iasi, Romania: LUMEN Publishing House, 2021)
In the national educational system of the Ukrainian diaspora of the USA and Canada the pre-school period covers the first stages of extra-familiar education, where establishing of child’s consciousness and connecting to spiritual values of the Ukrainian nation are taking place. Efficiency of this process depends on multiple factors. A significant role among them is played by didactic provision of educational-instructional process in pre-school educational institutions of various kinds whose main aim is to form national consciousness of the pupils through acquiring the Ukrainian language, as well as mastering contents of Ukrainian Studies subjects. Pedagogues at Ukrainian pre-school institutions in diaspora conditions clearly understand that the task of bringing up a child before the age of 6 implies providing them with various, beneficial for growing and useful for them, qualities. That is why teachers contribute to children acquiring such knowledge, abilities and skills which would help them to successfully prepare for elementary school in the future. Since the main task of Ukrainian pre-school education lies in development of a child’s personality by means of Ukrainian Culture studies, a pedagogue (teacher) has to know Ukrainian and all subjects well.
Keywords: children,; national education,; pre-school,; Ukrainian diaspora,; visual-audial method